2003
DOI: 10.1159/000070041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Maize/Legume Mixtures on Biochemical Indices in Rats

Abstract: Protein-energy malnutrition is one of the major public health problems in developing countries of the world due to prevailing socio-economic problems. This study aimed to observe the effect of formulated complementary blends on biochemical parameters of rats. Extruded complementary blends from maize fortified with cowpea or soybean at a level of 35% and 25% respectively were fed to 4 groups of rats for 28 days. Similarly, 3 other groups of rats were placed on casein, non-protein or rat pellet diet. Biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…Total protein levels in rats fed high-fructose diet or quinoa diet were within the normal range for total protein [29]. Albumin level in all rats was similar because diets which were used in our study were protein sufficient.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Total protein levels in rats fed high-fructose diet or quinoa diet were within the normal range for total protein [29]. Albumin level in all rats was similar because diets which were used in our study were protein sufficient.…”
Section: Discussionmentioning
confidence: 73%
“…Protein malnutrition is often associated with increased activity of alkaline phosphatase [29]. Obatolu et al [29] observed that malted maize and soybean caused significant increase in activity of alkaline phosphatase in comparison with non protein diet. This enzyme in non-specific and the interpretation of the results therefore is ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Low protein diet involves a reduction in the rate of protein synthesis in most body tissues (Wykes et al 1996). The increase in serum alanine aminotransferase (ALT) and alkaline phosphatase (ALP) in animals fed on a protein deficient diet, suggests hepatocellular dysfunctions (Tandon et al 1998;Obatolu et al 2003). The protein calorie malnutrition affects synthesis of the mRNA suggesting that a defect occurs at a pre-transcriptional level that results in reduced concentrations of mRNA (Adames et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The supplementation of the two diets with S. abyssinica significantly reduced the activity of transaminases, indicating that S. abyssinica leaves powder restored the function of liver during protein-energy malnutrition treatment. Indeed, the increase in serum alanine aminotransferase and alkaline phosphatase in animals fed with protein deficient diet suggests hepatocellular dysfunctions (Obatolu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%